Understanding the Antecedent of Behavioural Intention Towards Intention to Knowledge Sharing Behaviour among Non-Academic Employees in Indonesian Higher Learning Institutions: A Mixed Methods Approach - Husein, Alice Erni; Isa, Salmi Mohd; Situmorang, Zakarias (Journal of Ecohumanism, 2024)
This study investigated the factors influencing knowledge-sharing behaviour (KSB) among non-academic staff in higher learning institutions (HLIs) in Indonesia. Under the positivist research philosophy, the current study employs a quantitative research approach, where data were collected from 405 non-academic employees throughout private and public HLI in Indonesia. The findings of the online surveys were triangulated with the Focus Group Discussion (FGD) session. Utilizing the extended theory of planned behaviour (ETPB), key findings have indicated that only perceived behavioral control and altruism significantly influence the intention to knowledge sharing behavior (IKSB), while attitude and subjective norms demonstrated otherwise. Additionally, personal behaviour insignificantly influenced perceived behavioural control despite its significant influence on attitude. Similarly, trust exhibited an insignificant moderating effect on the relationship between attitude and IKSB. Lastly, IKSB significantly influenced the actual knowledge sharing behaviour (KSB). This study contributes to improving the quality of human resources in the context of Indonesian HLI, providing valuable and practical insights for policymakers in developing IKSB among non-academic employees. Policy implications and recommendations for future research were discussed accordingly.